Benchmarking Global Poverty Reduction - Ravallion, Martin (2013)
Against what standards should we judge the developing world's overall performance against poverty going forward? The paper proposes two measures, each with both "optimistic" and "ambitious" targets for 2022, 10 years from the time of writing. The first measure is absolute consumption poverty, as judged by what "poverty" means in the poorest countries. The second is a new measure of global poverty combining absolute poverty with country-specific social inclusion needs, consistently with national poverty lines. The optimistic benchmark would entail an absolute poverty rate of 9 percent in 2022, and a combined poverty rate of 40 percent, including the allowance for social inclusion. The more ambitious targets would bring the absolute rate down to 3 percent and the combined rate to 33 percent. The optimistic target would maintain the (impressive) progress against poverty of the last 20 years, without global crises to stall that progress. The ambitious target would require about a 1 percentage point higher growth rate for the gross domestic product of the developing world, as long as this did not come with a reduction in the household sector's share or any further increase in overall inequality beyond its level in 2008. Alternatively, the 3 percent target could be reached at currently expected growth rates but at the lower level of inequality found in 1999.